1983
DOI: 10.1001/archderm.119.8.677
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Treponema pallidum in a cutaneous gumma by indirect immunofluorescence

Abstract: Treponema pallidum was demonstrated in a cutaneous, tertiary syphilitic lesion by indirect immunofluorescence microscopy, but not by darkfield microscopy illumination or silver stain. The numerous organisms observed by this method may help explain the histologically vigorous tissue reaction in tertiary syphilis, despite the scarcity of organisms demonstrable by other methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…In support of this is an ultrastructural study that has demonstrated severe degradation of spirochetes in late lesions (257), and the infrequent detection of treponemal antigens or DNA in tertiary syphilis (41, 53, 56). This example of a gumma with abundant positive granular (destroyed treponemal cell wall) supports the contention that non-viable treponemal antigen is promoting the immune response.…”
Section: Figurementioning
confidence: 91%
See 3 more Smart Citations
“…In support of this is an ultrastructural study that has demonstrated severe degradation of spirochetes in late lesions (257), and the infrequent detection of treponemal antigens or DNA in tertiary syphilis (41, 53, 56). This example of a gumma with abundant positive granular (destroyed treponemal cell wall) supports the contention that non-viable treponemal antigen is promoting the immune response.…”
Section: Figurementioning
confidence: 91%
“…Therefore, the testing of syphilis in tissue and other bodily fluids offers another important method to diagnose cases of syphilis that escaped screening, or in cases where syphilis was not considered in the clinical differential diagnosis. Silver staining (Levaditi, Warthin-Starry, Steiner, or Dieterle stains), direct immunofluorescence, and immunohistochemistry are methods that can directly detect spirochetes in formalin fixed, paraffin embedded tissue, particularly when organisms are numerous, as is the case in chancres and early lesions of secondary syphilis (28, 3453). As syphilis progresses to latent and tertiary stages, spirochetes become scarce, so these methods fail, due to the detection limit being exceeded.…”
Section: An Historical Perspective Of the Pathology Of Syphilismentioning
confidence: 99%
See 2 more Smart Citations
“…Im Zentrum der Granulome können Nekrosen auftreten. Mit sensitiven Methoden [9] lassen sich zwar noch Treponemen in Gummen nachweisen,sie gelten jedoch nicht als infektiöse Läsionen.…”
Section: Klinik Der Syphilis -Tertiärstadiumunclassified